Prophetic Discourse in Islamic Educational Studies - Taufiq Taufiq (Universitas Muhammadiyah Surakarta, 2017)
This study discusses the prophetic discourse in the study of Islamic education. It is a library research focused on prophetic discourse and Islamic education. The prophetic theory developed by Kuntowijoyo was employed to reveal the prophetic dimension of Islamic education. The three prophetic dimensions of Islamic education are: humanization, liberation and transcendence. On this basis, this study affirms prophetic education as an alternative concept of Islamic education. However, prophetic education becomes a contextual education discourse of society change and seems to be less sensitive to the community development. Yet Islamic educational institutions can establish prophetic discourse as a form of ijtihad in the development of Islamic education.